2020
DOI: 10.1038/s41467-020-15685-z
|View full text |Cite
|
Sign up to set email alerts
|

A processive phosphorylation circuit with multiple kinase inputs and mutually diversional routes controls G1/S decision

Abstract: Studies on multisite phosphorylation networks of cyclin-dependent kinase (CDK) targets have opened a new level of signaling complexity by revealing signal processing routes encoded into disordered proteins. A model target, the CDK inhibitor Sic1, contains linear phosphorylation motifs, docking sites, and phosphodegrons to empower an N-to-C terminally directed phosphorylation process. Here, we uncover a signal processing mechanism involving multi-step competition between mutually diversional phosphorylation rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 72 publications
4
16
0
Order By: Relevance
“…We found that a construct based on the wild type Far1(1–150) was degraded rapidly, declining to 50% of its maximal levels by ~ 14 min from Start (Fig 1E). This is in good agreement with our previous observations of the timing of G1/S transition, marked by Sic1 degradation and accumulation of free Clb5‐Cdk1 complex (Venta et al , 2020). In contrast, a double‐alanine mutation of the di‐phosphodegron stabilized the sensor for the length of the cell cycle, which for budding yeast in rich media is about 90 min (Fig 1D and E).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We found that a construct based on the wild type Far1(1–150) was degraded rapidly, declining to 50% of its maximal levels by ~ 14 min from Start (Fig 1E). This is in good agreement with our previous observations of the timing of G1/S transition, marked by Sic1 degradation and accumulation of free Clb5‐Cdk1 complex (Venta et al , 2020). In contrast, a double‐alanine mutation of the di‐phosphodegron stabilized the sensor for the length of the cell cycle, which for budding yeast in rich media is about 90 min (Fig 1D and E).…”
Section: Resultssupporting
confidence: 94%
“…The reason for this could be the necessity to compromise between efficient phosphorylation and filtering the erroneous noisy peaks of kinase signals. Such diversional function of Cks1-driven multisite phosphorylation route is also reminiscent to our recent finding revealing that within the CDK-Sic1 inhibitor complex, two competing Cks1-dependent diversional routes and their various kinase inputs control the degron phosphorylation (Venta et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…The cooperativity that can be envisioned among Clb/Cdk1-dependent phosphorylation events on Fkh2 finds a parallel with studies that provided insights into the multisite phosphorylation mechanism that degrades Sic1 28 31 . We have shown that, similarly to Fkh2, Sic1 interacts with all Clb cyclins 32 and parallel studies have shown that a switch-like Sic1 destruction is dependent on a complex process in which both Cln2/Cdk1 (G1 phase) and Clb5/Cdk1 (S-phase) activities act in processive multi-phosphorylation steps 29 .…”
Section: Introductionmentioning
confidence: 93%
“…We showed that Sic1 releases Clb2 from Cdc6 which supports origin licensing (Figure 5). Sic1 contains multiple Cdk1 phosphorylation sites, which includes a phospho-threonine Cks1 docking site at the N-terminus (Kõivomägi et al, 2011;Venta et al, 2020). Cks1 docking triggers an N-to C-directed multisite phosphorylation cascade both in Sic1 and Cdc6, which results in the creation of phospho-degrons targeted by SCF Cdc4 (Örd et al, 2019;Venta et al, 2020).…”
Section: Sic1 Regulationmentioning
confidence: 99%
“…It has been suggested that Cdc6 acts as a CDK inhibitor together with Sic1 and Cdh1, a co-activator of the APC (Calzada et al, 2001). Sic1 and Cdc6 share similarities in Cdk1 inhibitory function, as both have been shown to associate cyclin-Cdk1 complexes with low nanomolar affinity which is partly facilitated by Cks1 docking (Örd et al, 2019;Venta et al, 2020). Deletion of the Cdc6 N-terminal Cdk1 site (cdc6Δ47) shows an elevated Clb2-Cdk1 activity in mitosis, indicating that Cdc6 Nterminus plays a role in Clb2-Cdk1 inhibition (Calzada et al, 2001).…”
mentioning
confidence: 99%